Biosocial foundations of family processes - Booth, Alan 1935-; McHale, Susan M.; Landale, Nancy S. (Springer eBooks., 2011)
Genes and environment. Biology and behavior. Nature and nurture. The terminology may be clear-cut, but the processes themselves are far from simple: unlike the direct cause-and-effect dichotomies of past frameworks, researchers now recognize these family-based connections as multifaceted, transactional, and emergent. Biosocial Foundations of Family Processes aims at illuminating a multiplicity of approaches and methodologies for studying family dynamics, to match the complex interplay of physiological factors, environmental challenges, and behavioral adaptations that characterize family life and development. Chapters illustrate physical and social influences on parenting, childhood, adolescence, fertility, and family formation, providing analytical frameworks for understanding key areas such as family behavior, health, development, and adaptation to contextual stressors. Highlights of the coverage: Motherhood and fatherhood as seen through psychobiological and functional perspectives The importance of the phenotype in studies of gene/environment interactions Adolescence: genes, hormones, and family behavior Psychological adaptation and human mating strategies Family resources, genes, and human development Social inequities, family relationships, and child health A book that explains the present while charting the future study of its subject, Biosocial Foundations of Family Processes is provocative reading for researchers in family relations, family sociology, psychology, and public health, and may hold particular interest for policymakers.